Profitability, Liquidity, Solvability, and Stock Price: Evidence from Consumer Goods Industry (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Fundamentally, the information from financial statements can be utilized to predict the stock price. Indeed, the information is its ratio covering profitability, liquidity, and solvability as the favorite ones. This research examines the tendency of three ratios toward stock price, where the population is from the Indonesian Capital Market-listed consumer goods companies between 2017 and 2021, and the eight samples are taken based on a purposive sampling technique. Because of five years, this study uses 40 observations. Furthermore, it tests the three hypotheses according to the regression model coefficients. In conclusion, this study demonstrates that profitability measured by return on equity and solvability quantified by debt to equity ratio positively affect the stock price. Meanwhile, the current ratio as the liquidity proxy does not influence this price.